Beyond the Score: A Personal Journey of Language Learning and Identity in IELTS Preparation - Ika Chairiyani; Iswandini Agustin (ETERNAL (English Teaching Journal), 2025)
This autoethnography study examines the author's experiences in language learning and identity formation as related to IELTS preparation. As an English teacher, the author faces the unexpected distance between teaching skill and ability in the usage of language and emphasizes the layered nature of linguistic proficiency. Through a critical examination of her own IELTS learning experience, the author reveals the emotional and psychological struggles of navigating standardized testing, including feelings of overwhelm and inadequacy. Through familiarity with IELTS materials and with taking the IELTS test, the author undertakes a self-revelatory adventure, in which a discourse between language learning, identity, and academic expectation emerges. This reflective narrative presents a complex explanation of the personal psycho-social process behind language acquisition and therefore, the reader is led beyond the score to a set of complex interactions of personal development, self-perception, and identity an academic sense. The findings emphasize the importance of self-regulated learning, social engagement, and cognitive strategies in shaping one's academic and linguistic identity.